Pengaruh Penerapan Due Professional Care dan Akuntabilitas Audit Internal terhadap Efektifitas Audit Internal dengan Masa Tugas Sebagai Variabel Moderasi: Studi pada Satuan Pengawas Internal Perguruan Tinggi Keagamaan Negeri di Indonesia - Bakri Bakri; Mahfiza Mahfiza (Al-Buhuts, 2023)
This study aims to analyse the effect of due professional care and internal auditor accountability on the effectiveness of internal audits, with auditor tenure as a moderating variable. The research method used is a quantitative approach with an explanatory survey design. Primary data were obtained by distributing questionnaires to internal auditors who are members of the Internal Audit Unit (SPI) of State Religious Universities (PTKN) in Indonesia using purposive sampling. Data analysis was performed using multiple linear regression and Moderated Regression Analysis (MRA). The results showed that due professional care and internal auditor accountability had a positive and significant effect on internal audit effectiveness. These findings indicate that auditors who exercise professional care and have a high level of accountability are able to improve the effectiveness of internal audits. Furthermore, the moderation test results show that the auditor's tenure strengthens the influence of due professional care on the effectiveness of internal audits because longer work experience allows auditors to apply professional prudence more consistently and effectively in various audit conditions. However, the auditor's tenure does not moderate the influence of accountability on internal audit effectiveness, indicating that auditor accountability is more influenced by professional values and organisational control systems than by the length of tenure. The implications of this study emphasise the importance of strengthening professional competence, accountable attitudes, and proportional management of internal auditor tenure to improve internal audit effectiveness. This research is expected to contribute theoretically to the development of public sector internal audit literature and serve as a practical reference for university leaders in strengthening internal oversight functions.